Porous silicon carbon material as well as preparation method and application thereof
By doping nanodiamond into the carbon cladding of porous silicon carbon materials, the problems of low first efficiency, large volume expansion and poor circulation rate performance of silicon materials in lithium batteries are solved, and the rate performance and cycle stability of the battery are improved and first effect enhance the temperature coefficient and mechanical properties of the material.
Patent Information
- Application Number
- CN202411292586.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-27
AI Technical Summary
The capacity of graphite negative electrode is close to its limit. As a new material for lithium battery negative electrode, silicon material has problems such as low first-term efficiency, large volume expansion, and poor circulation rate performance.
Porous silicon carbon materials are used, which include porous silicon carbon cores and carbon cladding layers. The carbon cladding layer is doped with nanodiamonds. By doping nanodiamonds on the surface of the porous silicon carbon core, it utilizes its high lithium adsorption capacity, low expansion coefficient and Large specific surface area improves the rate performance, cycle stability and first effect of the battery, and alleviates the side reaction between nanodiamond and electrolyte.
It improves the rate performance, cycle stability, first-effect and mechanical properties of lithium-ion batteries, reduces volume expansion, enhances the temperature coefficient of the material, and achieves higher lithium-ion migration speed and better battery performance.
Smart Images

Figure BDA0005045050440000171 
Figure BDA0005045050440000181 
Figure BDA0005045050440000191
Abstract
Description
Technical Field
[0001] The present application relates to the field of material technology, and in particular to a porous silicon-carbon material and a preparation method and application thereof. Background Art
[0002] The maximum theoretical capacity of graphite negative electrode is 372mAh / g. Now graphite material as lithium battery negative electrode has reached its capacity limit and it is difficult to increase it further in the future. The maximum theoretical capacity of silicon material is 4200mAh / g, which is much higher than graphite, and it has become a hot new material for battery negative electrode. However, silicon material has problems such as low first effect (i.e. first efficiency), large volume expansion, and poor cycle rate performance. Summary of the invention
[0003] Based on the defects of the prior art, the purpose of this application is to provide a porous silicon-carbon material and a preparation method and application thereof.
[0004] In order to achieve the above objectives, in a first aspect, the present application provides a porous silicon-carbon material, which includes a porous silicon-carbon core and a carbon coating layer disposed on the surface of the porous carbon-based core, wherein the carbon coating layer is doped with nanodiamonds (ND).
[0005] In some embodiments, the porous silicon carbon material satisfies: 4.3×10 -5 ≤X / BET≤9.5×10 -5 ;
[0006] Wherein, X is the ratio of the molar amount of the nanodiamond to the molar amount of the porous silicon carbon core;
[0007] BET 2 / g is the specific surface area of the porous silicon carbon core.
[0008] In some embodiments, the porous silicon carbon material satisfies: Z / BET<0.06;
[0009] Wherein, Z nm is the particle size Dv50 of the nanodiamond;
[0010] BET 2 / g is the specific surface area of the porous silicon carbon core.
[0011] In some embodiments, the porous silicon carbon material satisfies at least one of the following conditions:
[0012] S1.X=0.015-0.05, wherein X is the ratio of the molar amount of the nanodiamond to the molar amount of the porous silicon carbon core;
[0013] S2.BET=400~1000m 2 / g, where BET m2 / g is the specific surface area of the porous silicon carbon core;
[0014] S3.Z=10-25 nm, wherein Z nm is the particle size Dv50 of the nanodiamond.
[0015] In a second aspect, the present application provides a method for preparing the porous silicon-carbon material, which comprises the following steps:
[0016] The porous silicon-carbon material is obtained by mixing a mixture of nano-diamond and a liquid organic coating agent with a porous silicon-carbon core raw material, performing a first dispersion, and then performing a first calcination in an inert atmosphere.
[0017] Preferably, the method further comprises the following steps: mixing the porous silicon carbon material with an etching solution, dispersing the material for a second time, separating the solid from the liquid, collecting the solid, washing the solid and drying the solid, wherein the etching solution is an alkaline solution.
[0018] Preferably, the method for preparing the porous silicon-carbon material satisfies at least one of the following conditions:
[0019] S4. The total molar amount of the nano-diamond and the liquid organic coating agent in the mixture is 8% to 20% of the molar amount of the porous silicon-carbon core raw material;
[0020] S5. In the mixture of the nanodiamond and the liquid organic coating agent, the molar ratio of the nanodiamond and the liquid organic coating agent is (0.2 to 1.2): 1;
[0021] S6. The liquid organic coating agent in the mixture of the nanodiamond and the liquid organic coating agent comprises at least one of heterocyclic aromatic hydrocarbons, ketones, hydrocarbons, resins and asphalt;
[0022] S7. The residual carbon value of the liquid organic coating agent in the mixture of the nanodiamond and the liquid organic coating agent is 10% to 30%;
[0023] S8. The temperature of the first calcination is 300 to 400 ° C, and the time of the first calcination is 4 to 5h;
[0024] S9. The mass fraction of the alkaline substance in the etching solution is 5% to 10%;
[0025] S10. The ratio of the porous silicon carbon material to the etching solution is 5 g: (150-200) mL;
[0026] S11. The alkaline substance in the etching solution is a hydroxide, and the hydroxide includes at least one of potassium hydroxide and sodium hydroxide;
[0027] S12. The process parameters of the second dispersion are as follows: temperature 75-85°C, rotation speed 200-300rpm, time 20-24h.
[0028] Preferably, the method for preparing the porous silicon-carbon core raw material comprises the following steps:
[0029] Carbonizing a carbon source in an inert atmosphere, and screening the carbon source to obtain a first carbon material;
[0030] The obtained first carbon material is mixed and dispersed with a pore-forming agent, and calcined to obtain a second porous carbon material;
[0031] Purifying the obtained second porous carbon material to obtain a third porous carbon material;
[0032] Depositing silicon on the obtained third porous carbon material using a mixed gas of a protective gas and a silicon source gas to obtain the porous silicon-carbon core raw material;
[0033] The carbon source includes at least one of a biomass carbon source and a resin carbon source, the biomass carbon source includes at least one of coconut shells, rice husks and platycodon, and the resin carbon source includes at least one of a phenolic resin-based carbon source and an epoxy resin-based carbon source;
[0034] During the preparation of the first carbon material, the carbonization temperature is 570-30° C., the carbonization time is 4-8 hours, and the particle size Dv50 of the first carbon material is 10-14 μm;
[0035] In the process of preparing the second porous carbon material using the first carbon material, the pore-forming agent includes an alkaline solution, the molar ratio of the first carbon material to the alkaline substance in the alkaline solution is (4-5):(2-3), the concentration of the alkaline substance in the alkaline solution is 0.05-0.08 mol / L, the alkaline substance in the alkaline solution includes sodium hydroxide and potassium hydroxide, the mass ratio of sodium hydroxide to potassium hydroxide is (0.95-1.05):(0.95-1.05), the calcination temperature is 750-800°C, and the calcination time is 1-2h;
[0036] The step of purifying the second porous carbon material comprises: firstly washing the second porous carbon material with acid, then washing it with water until it is neutral, and then calcining it at a temperature of 500 to 600° C. for a time of 3 to 4 hours;
[0037] In the process of preparing the porous silicon-carbon core raw material by using the third porous carbon material, the molar ratio of the third porous carbon material to the silicon source gas is (4-4.3):1, and the flow rate of the silicon source gas is 1-2 m / s. 3 / h, the deposition temperature is 400-600°C, the deposition time is 4-7h, and the silicon source gas includes at least one of silicon tetrahydride and silicon dioxide.
[0038] In a third aspect, the present application provides a battery comprising a positive electrode plate and a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer comprises the porous silicon-carbon material.
[0039] In a fourth aspect, the present application further provides an electrical device, wherein the electrical device comprises the battery.
[0040] Compared with the prior art, the beneficial effect of the present application is that the present application utilizes nanodiamonds to improve the rate performance, cycle stability, first efficiency, temperature coefficient, etc. of the battery by doping nanodiamonds in the carbon coating layer on the surface of the porous silicon-carbon core. At the same time, doping nanodiamonds in the carbon coating layer can alleviate the dissolution behavior of nanodiamonds and the electrolyte. DETAILED DESCRIPTION
[0041] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.
[0042] According to a first aspect of the present application, a porous silicon-carbon material is provided, which includes a porous silicon-carbon core and a carbon coating layer disposed on the surface of the porous carbon-based core, wherein the carbon coating layer is doped with nanodiamonds.
[0043] The silicon-carbon core of the present application has a porous structure, which can alleviate the volume expansion of silicon-based materials; and by doping nanodiamonds in the carbon coating layer on the surface of the porous silicon-carbon core, first, by utilizing the properties of nanodiamonds such as high lithium adsorption capacity, low expansion coefficient and large specific surface area, not only more lithium ion adsorption sites are provided to achieve rapid lithium ion transmission, improve the rate performance and cycle stability of the battery, but also lithium ions can be induced to be better embedded in the negative electrode, avoiding the formation of lithium dendrites during charging and discharging while improving the first effect; second, nanodiamonds have a certain pressure resistance, which can play a role in pinning cracks, thereby improving mechanical properties, which is conducive to overcoming the problem of structural collapse during the charging and discharging process of lithium-ion batteries; third, doping nanodiamonds in the carbon coating layer can alleviate the side reactions between nanodiamonds and electrolytes and improve the cycle performance of the battery; fourth, nanodiamonds mixed in the carbon coating layer can also improve the temperature coefficient of the material, because diamonds have high hardness and good chemical stability, and the migration speed of lithium ions is relatively stable under different temperature environments, achieving the effect of 1+1>2. Among them, the temperature coefficient refers to the ratio of the discharge capacity of the battery cell at room temperature 25°C to the discharge capacity at high temperature 45°C.
[0044] In some embodiments, the porous silicon carbon material satisfies: 4.3×10 -5 ≤X / BET≤9.5×10 -5 ;
[0045] Wherein, X is the ratio of the molar amount of the nanodiamond to the molar amount of the porous silicon carbon core;
[0046] BET 2 / g is the specific surface area of the porous silicon carbon core.
[0047] When the porous silicon carbon material meets the following conditions: 4.3×10 -5 ≤X / BET≤9.5×10 -5 , if X / BET is 4.3×10 -5 , 4.5×10 -5 5.0×10 -5 , 6.0×10 -5 , 7.0×10 -5 , 8.0×10 -5 9.0×10 -5 , 9.5×10 -5 Or when it is within the range formed by any two of the above values, not only the cycle performance is better, but also the compaction density is high, the first efficiency is high, and the temperature coefficient is high; while ensuring that the porous silicon-carbon material has a high gram capacity, on the one hand, it is avoided that too little mixing will not significantly improve the first efficiency and temperature coefficient, and on the other hand, it is avoided that too much mixing will result in excessive loss of compaction density and expansion rate.
[0048] In some embodiments, the porous silicon carbon material satisfies: Z / BET<0.06;
[0049] Wherein, Z nm is the particle size Dv50 of the nanodiamond;
[0050] BET 2 / g is the specific surface area of the porous silicon carbon core.
[0051] When the porous carbon material satisfies: Z / BET<0.06, such as Z / BET of 0.059, 0.055, 0.05, 0.04, 0.03, 0.02, 0.01, 0.008 or a range formed by any two of the above values, the particle size Dv50 of the nanodiamond is more suitable, the negative electrode compaction density is higher, and the cycle performance is better. In one embodiment, 0.008 <Z / BET<0.06。
[0052] In some embodiments, X=0.015-0.05, wherein X is the ratio of the molar amount of nanodiamond to the molar amount of porous silicon carbon core. When X is 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05 or a range formed by any two of the above values, the doping amount of nanodiamond is more suitable, the compaction density is high, the side reaction between nanodiamond and electrolyte is less, the first effect and temperature coefficient are higher, and the cycle performance is better. X can be detected by nuclear magnetic resonance.
[0053] In some embodiments, BET=400-1000, where BET m 2 / g is the specific surface area of the porous silicon carbon core. When BET is 400-1000, such as 400, 500, 600, 700, 800, 900, 1000 or a range formed by any two of the above values, the porous structure of the porous silicon carbon is more suitable, and the first efficiency and energy density are more suitable.
[0054] In some embodiments, Z=10-25, wherein Z nm is the particle size Dv50 of the nanodiamond. Z can be selected as 10, 12, 15, 17, 20, 23, 25 or a range formed by any two of the above values. When Z=10-25, the D50 particle size of the diamond is more suitable, and the compaction density and cycle performance are better.
[0055] BET can be measured by the following method: place 5g of porous silicon carbon sample in 30-50mL of methanol, ultrasonically disperse for 30min to obtain the sample solution, and then use the specific surface area meter to test; before testing with the specific surface area meter, preheat the instrument for 20min, pretreat the sample solution with nitrogen for 10min, and then add the sample solution to the specific surface area meter for measurement.
[0056] Z can be determined using a laser particle size analyzer, which irradiates the nanodiamond sample with laser and uses the principle of light scattering to measure the size and distribution of the nanodiamond particles.
[0057] According to the second aspect of the present application, a method for preparing the above-mentioned porous silicon-carbon material is provided, which comprises the following steps:
[0058] The mixture of nano-diamond and liquid organic coating agent is mixed with porous silicon-carbon core raw material, and then dispersed for the first time, and then calcined for the first time in an inert atmosphere to obtain porous silicon-carbon material.
[0059] Liquid phase coating can achieve high-strength bonding between nano-diamond particles and the surface of the porous silicon-carbon core to form a dense coating layer, which is more conducive to improving the material's first efficiency, rate performance, cycle performance and temperature coefficient.
[0060] In some embodiments, the total molar amount of nanodiamonds and liquid organic coating agents in the mixture of nanodiamonds and liquid organic coating agents is 8% to 20% of the molar amount of the porous silicon-carbon core raw material, such as 8%, 10%, 15%, 20% or a range formed by any two ratios thereof.
[0061] In some embodiments, in the mixture of nanodiamond and liquid organic coating agent, the molar ratio of nanodiamond to liquid organic coating agent is (0.2-1.2):1, such as 0.2:1, 0.3:1, 0.5:1, 0.6:1, 0.8:1, 1:1, 1.2:1 or a range formed by any two of the above ratios. When the molar ratio of nanodiamond to liquid organic coating agent is (0.2-1.2), especially (0.3-0.6):1, the content of nanodiamond in the carbon coating layer is more suitable and the cycle performance is better.
[0062] In some embodiments, the liquid organic coating agent in the mixture of nanodiamond and liquid organic coating agent includes at least one of heterocyclic aromatic hydrocarbons, ketones, hydrocarbons, resins and asphalt. Exemplarily, the heterocyclic aromatic hydrocarbons include at least one of thiophene, furan, cytosine ring compound atoms butadiene, etc.; ketones include at least one of methyl ketone, acetone, etc.; hydrocarbons include at least one of alkanes, cycloalkanes, alkenes, alkynes, etc.; resins include at least one of epoxy resins, phenolic resins, polyether esters, etc.
[0063] In some embodiments, the residual carbon value of the liquid organic coating agent is 10% to 20%, which is controlled within this range to achieve a better coating effect after carbonization. The residual carbon value of the liquid organic coating agent can be measured by the following method: the calculation formula of the residual carbon value X% is X=G1 / G×100%, where G1 is the weight of the residue after the liquid organic coating agent is calcined at 300°C for 3h in a nitrogen atmosphere, in grams; G is the weight of the liquid organic coating agent before calcination, in grams.
[0064] In some embodiments, the temperature of the first calcination is 300-400°C, and the time of the first calcination is 4-5 hours. The temperature of the first calcination can be selected as 300°C, 320°C, 340°C, 360°C, 380°C, 400°C or a range formed by any two ratios thereof; the time of the first calcination can be selected as 4h, 4.2h, 4.5h, 4.8h, 5h or a range formed by any two ratios thereof.
[0065] In some embodiments, the preparation method of the mixture of the nano-diamond and the liquid organic coating agent comprises the following steps: mixing the nano-diamond and the liquid organic coating agent, and ultrasonically dispersing to obtain a mixture of the nano-diamond and the liquid organic coating agent. Ultrasonic dispersion can make the nano-diamond better dispersed in the liquid organic coating agent. In one embodiment, the temperature of ultrasonic dispersion is 22 to 28°C, the ultrasonic frequency of ultrasonic dispersion is 50 to 80 Hz, the ultrasonic power of ultrasonic dispersion is 2000 to 3000 W, and the ultrasonic dispersion time is 3 to 4 hours.
[0066] By mixing the mixture of nano-diamond and liquid organic coating agent with the porous silicon carbon core raw material and performing the first dispersion, the nano-diamond can be more evenly distributed on the surface of the porous silicon carbon core along with the liquid organic coating agent. In some embodiments, the first dispersion is performed at 22-28° C., at a rotation speed of 3000-3500 rpm, and for 3-4 hours.
[0067] The first calcination is carried out in an inert atmosphere, such as a nitrogen atmosphere or an argon atmosphere.
[0068] In some embodiments, the method for preparing the porous silicon-carbon material further includes the following steps: mixing the obtained porous silicon-carbon material with an etching solution, dispersing it for a second time, separating the solid from the liquid, collecting the solid, washing and drying it, wherein the etching solution is an alkaline solution.
[0069] Etching the surface of the carbon coating with an etching solution can make the material softer, which is beneficial to increasing the compaction density and improving the energy density of the battery.
[0070] The mass fraction of the alkaline substance in the etching solution can be selected to be 1% to 20%, such as 1%, 3%, 5%, 7%, 10%, 12%, 15%, 17%, 20% or a range formed by any two ratios thereof. When the mass fraction of the alkaline substance in the etching solution is 1% to 20%, especially 5% to 10%, it not only helps to obtain a higher compaction density, but also avoids the excessive specific surface area of the porous silicon-carbon material, thereby making the first efficiency higher, the side reactions less, the by-products less, and the cycle performance better.
[0071] In one embodiment, the ratio of the porous silicon carbon material to the etching solution is 5g:(150-200)mL, such as 5g:150mL, 160mL, 180mL, 190mL, 200mL or a range formed by any two ratios thereof.
[0072] In one embodiment, the process parameters of the second dispersion are as follows: temperature 75-85°C, rotation speed 200-300rpm, time 20-24h. The temperature of the second dispersion can be selected as 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, or a range formed by any two ratios thereof; the rotation speed of the second dispersion can be selected as 200rpm, 220rpm, 240rpm, 260rpm, 280rpm, 300rpm, or a range formed by any two ratios thereof; the time of the second dispersion can be selected as 20h, 21h, 22h, 23h, 24h, or a range formed by any two ratios thereof.
[0073] The porous silicon-carbon core raw material can be prepared by a conventional method for preparing porous silicon-carbon materials in the art. In some embodiments, the method for preparing the porous silicon-carbon core raw material comprises the following steps:
[0074] Carbonizing a carbon source in an inert atmosphere, and screening the carbon source to obtain a first carbon material;
[0075] The obtained first carbon material is mixed and dispersed with a pore-forming agent, and calcined to obtain a second porous carbon material;
[0076] Purifying the obtained second porous carbon material to obtain a third porous carbon material;
[0077] Silicon is deposited on the third porous carbon material using a mixture of protective gas and silicon source gas to obtain the porous silicon-carbon core raw material. The porous silicon-carbon core raw materials prepared in these embodiments have micropores, mesopores and macropores inside, which can alleviate the volume expansion of silicon-based materials.
[0078] In one embodiment, the carbon source includes at least one of a biomass carbon source and a resin carbon source. Exemplarily, the biomass carbon source includes at least one of coconut shell, rice husk and platycodon, and the resin carbon source includes at least one of a phenolic resin-based carbon source and an epoxy resin-based carbon source.
[0079] In one of the embodiments, during the preparation of the first carbon material, the carbonization temperature is 570-700°C and the carbonization time is 4-8h. While ensuring that the carbon source is more fully carbonized, the content of heteroatoms (such as oxygen atoms) is lower, and the material has a higher initial efficiency, the porous silicon-carbon core raw material structure is avoided from being too loose, and the structural stability and pressure resistance are better.
[0080] In one embodiment, the particle size Dv50 of the first carbon material is 10-14 μm.
[0081] Carbonizing the carbon source in an inert atmosphere can isolate oxygen in the air and protect the carbon matrix, wherein the inert atmosphere can be selected as a nitrogen atmosphere or an argon atmosphere.
[0082] In the process of preparing the second porous carbon material using the first carbon material, the pore-forming agent can be either an alkaline solution or an acidic solution. The alkaline substance in the alkaline solution can be selected to include at least one of lithium hydroxide, sodium hydroxide and potassium hydroxide; the acidic solution can be selected to include at least one of sulfuric acid and hydrochloric acid. Compared with alkaline solutions, acidic solutions are more corrosive. Considering safety issues, it is preferred that the pore-forming agent is an alkaline solution.
[0083] In one embodiment, the pore former includes an alkaline solution, and the molar ratio of the first carbon material to the alkaline substance in the alkaline solution is (4-5):(2-3), such as 4:3, 5:3, 2:1, 5:2, or a range formed by any two of the above ratios.
[0084] In one embodiment, the concentration of the alkaline substance in the alkaline solution is 0.05-0.08 mol / L. When the alkaline substance in the alkaline solution includes sodium hydroxide and potassium hydroxide, and the mass ratio of sodium hydroxide to potassium hydroxide is (0.95-1.05):(0.95-1.05), a more alkaline mixed liquid can be obtained.
[0085] In one embodiment, in the process of preparing the second porous carbon material by using the first carbon material, the calcination temperature is 750-800° C., and the calcination time is 1-2 hours.
[0086] In some embodiments, the step of purifying the second porous carbon material includes: first acid-washing the second porous carbon material, then washing it with water until it is neutral, and then calcining it at a temperature of 500-600° C. for 3-4 hours.
[0087] In some embodiments, in the process of preparing the porous silicon-carbon core raw material using the third porous carbon material, the molar ratio of the third porous carbon material to the silicon source gas is (4-4.3):1, and the flow rate of the silicon source gas is 1-2 m / s. 3 / h, the deposition temperature is 400-600° C., and the deposition time is 4-7 hours. Exemplarily, the silicon source gas includes silicon tetrahydride.
[0088] According to a third aspect of the present application, a battery is provided, comprising a positive electrode plate and a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer comprises the above-mentioned porous silicon-carbon material.
[0089] In some embodiments, the mass fraction of the porous silicon-carbon material in the negative electrode active material layer is 95.0% to 96.0%, such as 95.0%, 95.5%, 95.7%, 96.0% or a range formed by any two of the above values.
[0090] In some embodiments, the negative electrode active material layer further includes a binder. The mass fraction of the binder in the negative electrode active material layer can be selected to be 2.5% to 3.3%, such as 2.5%, 2.7%, 3.0%, 3.3% or a range formed by any two of the above values. The binder can be selected to include at least one of PVDF and SBR.
[0091] In some embodiments, the negative electrode active material layer further includes a conductive agent. The mass fraction of the conductive agent in the negative electrode active material layer can be selected to be 0.7% to 2.5%, such as 0.7%, 1.0%, 1.5%, 2.0%, 2.5% or a range formed by any two of the above values. The conductive agent can be selected to include at least one of carbon black and carbon nanotubes.
[0092] The negative electrode current collector may be any conventional negative electrode current collector in the art, such as copper foil.
[0093] The positive electrode plate may also be any conventional positive electrode plate in the art, such as a lithium ion battery positive electrode plate or a sodium ion positive electrode plate.
[0094] According to a fourth aspect of the present application, there is provided an electric device, which includes the above-mentioned battery. The above-mentioned battery can be used as a power supply for the electric device. Exemplarily, the electric device includes at least one of an electric car and a mobile phone battery.
[0095] The present application is further described below in conjunction with specific embodiments.
[0096] Example 1
[0097] This embodiment provides a method for preparing a porous silicon-carbon material, which comprises the following steps:
[0098] The carbon source is carbonized in a nitrogen atmosphere at a carbonization temperature of 600° C. for a carbonization time of 5 h, and sieved to obtain a first carbon material with a particle size Dv50 of 12 μm, wherein the carbon source is coconut shell;
[0099] The obtained first carbon material and a pore-forming agent are mixed and dispersed, and placed in a tubular furnace into which nitrogen gas is introduced, and calcined at 780° C. for 1 hour, wherein the pore-forming agent is a mixed solution of sodium hydroxide and potassium hydroxide, the mass ratio of sodium hydroxide to potassium hydroxide is 1:1, and the molar ratio of the first carbon material to the alkaline substance in the pore-forming agent is 5:3, to obtain a second porous carbon material;
[0100] The obtained second porous carbon material is firstly acid-washed, then washed with water until neutral, and then calcined at 500° C. for 4 h to obtain a third porous carbon material;
[0101] The obtained third porous carbon material is placed in a rotary kiln, and nitrogen and silicon tetrahydride gas are introduced to deposit silicon on the third porous carbon material to obtain a porous silicon-carbon core raw material, wherein the molar ratio of the third porous carbon material to the silicon tetrahydride gas is 4:1, and the flow rate of the silicon tetrahydride gas is 2m 3 / h, the deposition temperature is 500℃, and the deposition time is 5h;
[0102] The nano-diamond and the liquid organic coating agent are mixed in a molar ratio of 0.3:1, and ultrasonically dispersed for 3 hours at room temperature (25° C.) under the conditions of an ultrasonic frequency of 80 Hz and a power of 2500 W to obtain a mixture of the nano-diamond and the liquid organic coating agent, wherein the nano-diamond particle size Dv50 is 10 nm, and the liquid organic coating agent is an epoxy resin with a residual carbon value of 30%;
[0103] The obtained mixture of nano-diamond and liquid organic coating agent is mixed and dispersed with the obtained porous silicon-carbon core raw material in a ratio that the total molar amount of nano-diamond and liquid organic coating agent is 10% of the molar amount of porous silicon-carbon core, and then calcined at 300° C. for 4 hours in a nitrogen atmosphere to obtain a porous silicon-carbon material semi-finished product;
[0104] The obtained porous silicon-carbon material semi-finished product was mixed with the etching solution in a ratio of 10 g: 300 mL, stirred at 80°C and 250 rpm for 24 hours, vacuum filtered, and the obtained solid was repeatedly washed with distilled water until the pH value of the filtrate reached 7, and then dried in a vacuum oven at 80°C for 12 hours to obtain a finished porous silicon-carbon material, wherein the etching solution was a KOH solution, and its KOH mass fraction was 5%.
[0105] Example 2
[0106] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 1 in that:
[0107] In the process of preparing the second porous carbon material using the first carbon material, the calcination time is 1.5 h;
[0108] In the process of preparing the mixture of nano-diamond and liquid-phase organic coating agent, the nano-diamond and the liquid-phase organic coating agent are mixed at a molar ratio of 0.42:1;
[0109] In the process of preparing a porous silicon-carbon material semi-finished product using a porous silicon-carbon core raw material, the total molar amount of nanodiamonds and liquid organic coating agents in the mixture of nanodiamonds and liquid organic coating agents used is 10.92% of the molar amount of the porous silicon-carbon core (the molar ratio of the liquid organic coating agent to the porous silicon-carbon core in the mixture of nanodiamonds and liquid organic coating agents is the same as that in Example 1).
[0110] Example 3
[0111] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 1 in that:
[0112] In the process of preparing the second porous carbon material using the first carbon material, the calcination time is 2 hours;
[0113] In the process of preparing the mixture of nano-diamond and liquid-phase organic coating agent, the nano-diamond and the liquid-phase organic coating agent are mixed at a molar ratio of 0.48:1;
[0114] In the process of preparing a porous silicon-carbon material semi-finished product using a porous silicon-carbon core raw material, the total molar amount of nanodiamonds and liquid organic coating agents in the mixture of nanodiamonds and liquid organic coating agents used is 11.38% of the molar amount of the porous silicon-carbon core (the molar ratio of the liquid organic coating agent to the porous silicon-carbon core in the mixture of nanodiamonds and liquid organic coating agents is the same as that in Example 1).
[0115] Example 4
[0116] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 1 in that:
[0117] In the process of preparing the second porous carbon material using the first carbon material, the calcination time is 3 hours;
[0118] In the process of preparing the mixture of nano-diamond and liquid-phase organic coating agent, the nano-diamond and the liquid-phase organic coating agent are mixed at a molar ratio of 0.60:1;
[0119] In the process of preparing a porous silicon-carbon material semi-finished product using a porous silicon-carbon core raw material, the total molar amount of nanodiamonds and liquid organic coating agents in the mixture of nanodiamonds and liquid organic coating agents used is 12.31% of the molar amount of the porous silicon-carbon core (the molar ratio of the liquid organic coating agent to the porous silicon-carbon core in the mixture of nanodiamonds and liquid organic coating agents is the same as that in Example 1).
[0120] Example 5
[0121] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 1 in that:
[0122] In the process of preparing the mixture of nano-diamond and liquid-phase organic coating agent, the nano-diamond and the liquid-phase organic coating agent are mixed in a molar ratio of 0.5:1;
[0123] In the process of preparing a porous silicon-carbon material semi-finished product using a porous silicon-carbon core raw material, the total molar amount of nanodiamonds and liquid organic coating agents in the mixture of nanodiamonds and liquid organic coating agents used is 11.54% of the molar amount of the porous silicon-carbon core (the molar ratio of the liquid organic coating agent to the porous silicon-carbon core in the mixture of nanodiamonds and liquid organic coating agents is the same as that in Example 1).
[0124] Example 6
[0125] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 1 in that:
[0126] In the process of preparing the mixture of nano-diamond and liquid-phase organic coating agent, the nano-diamond and the liquid-phase organic coating agent are mixed in a molar ratio of 0.6:1;
[0127] In the process of preparing a porous silicon-carbon material semi-finished product using a porous silicon-carbon core raw material, the total molar amount of nanodiamonds and liquid organic coating agents in the mixture of nanodiamonds and liquid organic coating agents used is 12.31% of the molar amount of the porous silicon-carbon core (the molar ratio of the liquid organic coating agent to the porous silicon-carbon core in the mixture of nanodiamonds and liquid organic coating agents is the same as that in Example 1).
[0128] Example 7
[0129] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 1 in that:
[0130] In the process of preparing the mixture of nano-diamond and liquid-phase organic coating agent, the nano-diamond and the liquid-phase organic coating agent are mixed in a molar ratio of 0.1:1;
[0131] In the process of preparing a porous silicon-carbon material semi-finished product using a porous silicon-carbon core raw material, the total molar amount of nanodiamonds and liquid organic coating agents in the mixture of nanodiamonds and liquid organic coating agents used is 8.46% of the molar amount of the porous silicon-carbon core (the molar ratio of the liquid organic coating agent to the porous silicon-carbon core in the mixture of nanodiamonds and liquid organic coating agents is the same as that in Example 1).
[0132] Example 8
[0133] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 1 in that:
[0134] In the process of preparing the mixture of nano-diamond and liquid organic coating agent, the nano-diamond and the liquid organic coating agent are mixed in a molar ratio of 1.12:1;
[0135] In the process of preparing a porous silicon-carbon material semi-finished product using a porous silicon-carbon core raw material, the total molar amount of nanodiamonds and liquid organic coating agents in the mixture of nanodiamonds and liquid organic coating agents used is 16.31% of the molar amount of the porous silicon-carbon core (the molar ratio of the liquid organic coating agent to the porous silicon-carbon core in the mixture of nanodiamonds and liquid organic coating agents is the same as that in Example 1).
[0136] Example 9
[0137] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 4 in that:
[0138] In the process of preparing the mixture of nano-diamond and liquid organic coating agent, the nano-diamond and the liquid organic coating agent are mixed in a molar ratio of 0.3:1;
[0139] In the process of preparing a porous silicon-carbon material semi-finished product using a porous silicon-carbon core raw material, the total molar amount of nanodiamonds and liquid organic coating agents in the mixture of nanodiamonds and liquid organic coating agents used is 10% of the molar amount of the porous silicon-carbon core (the molar ratio of the liquid organic coating agent to the porous silicon-carbon core in the mixture of nanodiamonds and liquid organic coating agents is the same as that in Example 4).
[0140] Example 10
[0141] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 1 in that:
[0142] In the process of preparing the second porous carbon material using the first carbon material, the calcination time is 1 hour;
[0143] In the process of preparing the mixture of nano-diamond and liquid-phase organic coating agent, the nano-diamond and the liquid-phase organic coating agent are mixed at a molar ratio of 0.60:1;
[0144] In the process of preparing a porous silicon-carbon material semi-finished product using a porous silicon-carbon core raw material, the total molar amount of nanodiamonds and liquid organic coating agents in the mixture of nanodiamonds and liquid organic coating agents used is 12.31% of the molar amount of the porous silicon-carbon core (the molar ratio of the liquid organic coating agent to the porous silicon-carbon core in the mixture of nanodiamonds and liquid organic coating agents is the same as that in Example 1).
[0145] Embodiment 11
[0146] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 6 in that:
[0147] In the process of preparing the finished porous silicon-carbon material from the obtained porous silicon-carbon material semi-finished product, the etching solution used is a KOH solution, and the KOH mass fraction thereof is 9%.
[0148] Example 12
[0149] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 11 in that:
[0150] In the process of preparing the mixture of nano-diamond and liquid organic coating agent, the nano-diamond particle size Dv50 used is 20nm.
[0151] Embodiment 13
[0152] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 11 in that:
[0153] In the process of preparing the mixture of nano-diamond and liquid organic coating agent, the nano-diamond particle size Dv50 used is 25nm.
[0154] Embodiment 14
[0155] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 11 in that:
[0156] In the process of preparing the mixture of nano-diamond and liquid organic coating agent, the nano-diamond particle size Dv50 used is 35nm.
[0157] Embodiment 15
[0158] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 4 in that:
[0159] In the process of preparing the mixture of nano-diamond and liquid organic coating agent, the nano-diamond particle size Dv50 used is 55nm.
[0160] Example 16
[0161] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 4 in that:
[0162] In the process of preparing the mixture of nano-diamond and liquid organic coating agent, the nano-diamond particle size Dv50 used is 70nm.
[0163] Embodiment 17
[0164] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 4 in that:
[0165] In the process of preparing the mixture of nanodiamond and liquid organic coating agent, the nanodiamond particle size Dv50 used is 50nm;
[0166] In the process of preparing the finished porous silicon-carbon material by using the obtained porous silicon-carbon material semi-finished product, the etching solution used is a KOH solution, and the KOH mass fraction thereof is 7%.
[0167] Embodiment 18
[0168] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 6 in that:
[0169] In the process of preparing the finished porous silicon-carbon material from the obtained porous silicon-carbon material semi-finished product, the etching solution used is water.
[0170] Embodiment 19
[0171] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 6 in that:
[0172] In the process of preparing the finished porous silicon-carbon material by using the obtained porous silicon-carbon material semi-finished product, the etching solution used is a KOH solution, and the KOH mass fraction thereof is 20%.
[0173] Embodiment 20
[0174] This embodiment provides a method for preparing a porous silicon-carbon material, which differs from Embodiment 1 in that:
[0175] In the process of preparing the second porous carbon material using the first carbon material, the calcination time is 0.5h;
[0176] In the process of preparing the mixture of nano-diamond and liquid organic coating agent, the nano-diamond and the liquid organic coating agent are mixed in a molar ratio of 0.24:1;
[0177] In the process of preparing a porous silicon-carbon material semi-finished product using a porous silicon-carbon core raw material, the total molar amount of nanodiamonds and liquid organic coating agents in the mixture of nanodiamonds and liquid organic coating agents used is 9.54% of the molar amount of the porous silicon-carbon core (the molar ratio of the liquid organic coating agent to the porous silicon-carbon core in the mixture of nanodiamonds and liquid organic coating agents is the same as that in Example 1).
[0178] Comparative Example 1
[0179] This comparative example provides a method for preparing a porous silicon-carbon material, which differs from Example 1 in that:
[0180] A mixture of nanodiamond and liquid organic capping agent was not prepared;
[0181] In the process of preparing a porous silicon-carbon material semi-finished product using the obtained porous silicon-carbon core raw material, an equal amount of a liquid organic coating agent is used to completely replace the mixture of nanodiamond and the liquid organic coating agent, that is, the liquid organic coating agent and the obtained porous silicon-carbon core raw material are mixed and dispersed in a molar ratio of 1:10%, and then calcined at 300° C. for 4 hours in a nitrogen atmosphere to obtain a porous silicon-carbon material semi-finished product, and the liquid organic coating agent used is an epoxy resin with a residual carbon value of 30%;
[0182] The obtained porous silicon-carbon material semi-finished product is not treated with an etching solution, that is, the obtained porous silicon-carbon material semi-finished product is a finished porous silicon-carbon material.
[0183] Comparative Example 2
[0184] This comparative example provides a method for preparing a porous silicon-carbon material, which differs from Example 1 in that:
[0185] A mixture of nanodiamond and liquid organic capping agent was not prepared;
[0186] In the process of preparing a porous silicon-carbon material semi-finished product using the obtained porous silicon-carbon core raw material, an equal amount of a liquid organic coating agent is used to completely replace the mixture of nanodiamond and the liquid organic coating agent, that is, the liquid organic coating agent and the obtained porous silicon-carbon core raw material are mixed and dispersed in a molar ratio of 1:10%, and then calcined at 300°C in a nitrogen atmosphere for 4 hours to obtain a porous silicon-carbon material semi-finished product, and the liquid organic coating agent used is an epoxy resin with a residual carbon value of 30%.
[0187] The finished porous silicon-carbon materials obtained in the above-mentioned embodiments and comparative examples are made into full batteries according to the following method:
[0188] Porous silicon-carbon material is used as negative electrode active material, PVDF is used as binder, and carbon black is used as conductive agent. The three are mixed and dispersed in a mass ratio of negative electrode active material: binder: conductive agent = 95.5:3.3:1.2, and coated on both sides of the copper foil current collector. After drying, pressing and cutting, the negative electrode sheet is obtained;
[0189] Lithium cobalt oxide is used as the positive electrode active material, PVDF is used as the binder, and carbon black is used as the conductive agent. The three are mixed and dispersed in a mass ratio of positive electrode active material: binder: conductive agent = 94.5:1.3:4.2, and coated on both sides of the aluminum foil current collector. The positive electrode sheet is obtained after drying, pressing and cutting.
[0190] Using PE as the separator, the positive and negative electrodes were placed in the order of positive electrode / separator / negative electrode from top to bottom, and then wound into a 383450P soft-pack battery cell. After the battery cell was encapsulated with aluminum-plastic film, an appropriate amount of electrolyte (1 mol / L LiPF6 / DMC) was injected from the battery cell injection port under argon protection.
[0191] The following performance tests were performed on the above full battery:
[0192] Compacted density of porous silicon-carbon materials: using conventional powder compaction density tester equipment, during the test, pressurize the powder to 5 tons and maintain the pressure for 30 seconds, then remove the pressure, use a vernier caliper to measure the change in powder thickness, and then calculate the compacted density. This is a measurement method that uses pressure relief;
[0193] First effect: 3C charging to 100% SOC, then discharging at 5C to 0% SOC for a complete cycle test. The ratio of the discharge capacity to the charge capacity in the initial cycle of 1 week is the first effect.
[0194] Cycle performance: 3C charging to 100% SOC, then 5C discharge to 0% SOC for a complete cycle test. After the initial cycle is completed for one week, the full charge thickness V0 and the first cycle discharge capacity C0 are recorded. After 700 cycles of testing, the discharge capacity C of the soft-pack battery at 100% SOC and the full charge thickness V, capacity retention rate = C / C0*100%, volume expansion rate = (V-V0) / V0;
[0195] Temperature coefficient: The discharge capacity of the battery cell at room temperature 25°C and high temperature 45°C are tested respectively. The test method is the same as the first-effect test method. The temperature coefficient = the ratio of the discharge capacity at room temperature 25°C to the discharge capacity at high temperature 45°C.
[0196] The above test results are shown in Table 1, where BET m 2 / g is the specific surface area of the porous silicon carbon core; X is the ratio of the molar amount of nanodiamond to the molar amount of the porous silicon carbon core; Z nm is the particle size Dv50 of the nanodiamond, and P% is the mass fraction of hydroxide in the etching solution.
[0197] Table 1
[0198]
[0199]
[0200]
[0201] From the above data, it can be seen that the compaction density of the negative electrode in each embodiment is 0.98g / cm 3 The first efficiency is above 75%, the capacity retention rate after 700 cycles is above 75%, the volume expansion rate after 700 cycles is below 18.0%, and the temperature coefficient is above 97.6%.
[0202] In Comparative Examples 1 and 2, since the carbon coating layer of the porous silicon-carbon material products obtained is not doped with nanodiamonds, the first efficiency and temperature coefficient are both low, and the cycle performance is poor.
[0203] Comparison of Examples 1, 4 to 10 shows that when X / BET is 4.3×10 -5 ~9.5×10 -5 When it is within the range, it is more conducive to achieving a balance among the first efficiency, temperature coefficient, negative electrode compaction density and cycle performance. While obtaining a higher first efficiency and temperature coefficient, the negative electrode compaction density is higher and the cycle performance is better.
[0204] Comparative Examples 11 to 14, and Comparative Examples 4, 15 to 16 show that when Z / BET<0.06, it is beneficial to obtain a higher compaction density, first effect and better cycle performance.
[0205] By comparing Examples 6, 11, and 17 to 19, it can be seen that when the mass fraction of the alkaline substance in the etching solution is in the range of 5% to 10%, it is helpful to improve the compaction density and the cycle performance.
[0206] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A porous silicon-carbon material, characterized in that: It comprises a porous silicon-carbon core and a carbon coating layer arranged on the surface of the porous carbon-based core, wherein the carbon coating layer is doped with nano-diamonds.
2. The porous silicon-carbon material according to claim 1, characterized in that: Satisfaction: 4.3×10 -5 ≤X / BET≤9.5×10 -5 ; Wherein, X is the ratio of the molar amount of the nanodiamond to the molar amount of the porous silicon carbon core; BET 2 / g is the specific surface area of the porous silicon carbon core.
3. The porous silicon-carbon material according to claim 1, characterized in that: Satisfy: Z / BET<0.06; Wherein, Z nm is the particle size Dv50 of the nanodiamond; BET 2 / g is the specific surface area of the porous silicon carbon core.
4. The porous silicon-carbon material according to claim 1, characterized in that: At least one of the following conditions is met: S1.X=0.015-0.05, wherein X is the ratio of the molar amount of the nanodiamond to the molar amount of the porous silicon carbon core; S2.BET=400~1000m 2 / g, where BETm 2 / g is the specific surface area of the porous silicon carbon core; S3.Z=10-25 nm, wherein Z nm is the particle size Dv50 of the nanodiamond.
5. A method for preparing a porous silicon-carbon material as claimed in claim 1, characterized in that: The following steps are involved: The porous silicon-carbon material is obtained by mixing a mixture of nano-diamond and a liquid organic coating agent with a porous silicon-carbon core raw material, performing a first dispersion, and then performing a first calcination in an inert atmosphere.
6. The method for preparing the porous silicon-carbon material according to claim 5, characterized in that: The following steps are also included: The porous silicon-carbon material is mixed with an etching solution and then dispersed for a second time, the solid and the liquid are separated, and the solid is collected for washing and drying, wherein the etching solution is an alkaline solution.
7. The method for preparing a porous silicon-carbon material according to claim 6, characterized in that: At least one of the following conditions is met: S4. The total molar amount of the nano-diamond and the liquid organic coating agent in the mixture is 8% to 20% of the molar amount of the porous silicon-carbon core raw material; S5. In the mixture of the nanodiamond and the liquid organic coating agent, the molar ratio of the nanodiamond and the liquid organic coating agent is (0.2 to 1.2): 1; S6. The liquid organic coating agent in the mixture of the nanodiamond and the liquid organic coating agent comprises at least one of heterocyclic aromatic hydrocarbons, ketones, hydrocarbons, resins and asphalt; S7. The residual carbon value of the liquid organic coating agent in the mixture of the nanodiamond and the liquid organic coating agent is 10% to 30%; S8. The temperature of the first calcination is 300 to 400 ° C, and the time of the first calcination is 4 to 5h; S9. The mass fraction of the alkaline substance in the etching solution is 5% to 10%; S10. The ratio of the porous silicon carbon material to the etching solution is 5 g: (150-200) mL; S11. The alkaline substance in the etching solution is a hydroxide, and the hydroxide includes at least one of potassium hydroxide and sodium hydroxide; S12. The process parameters of the second dispersion are as follows: temperature 75-85°C, rotation speed 200-300rpm, time 20-24h.
8. The method for preparing the porous silicon-carbon material according to claim 5, characterized in that: The method for preparing the porous silicon-carbon core raw material comprises the following steps: Carbonizing a carbon source in an inert atmosphere, and screening the carbon source to obtain a first carbon material; The obtained first carbon material is mixed and dispersed with a pore-forming agent, and calcined to obtain a second porous carbon material; Purifying the obtained second porous carbon material to obtain a third porous carbon material; Depositing silicon on the obtained third porous carbon material using a mixed gas of a protective gas and a silicon source gas to obtain the porous silicon-carbon core raw material; Preferably, the carbon source comprises at least one of a biomass carbon source and a resin carbon source, the biomass carbon source comprises at least one of coconut shell, rice husk and platycodon, and the resin carbon source comprises at least one of a phenolic resin-based carbon source and an epoxy resin-based carbon source; Preferably, during the preparation of the first carbon material, the carbonization temperature is 570-700° C., the carbonization time is 4-8 hours, and the particle size Dv50 of the first carbon material is 10-14 μm; Preferably, in the process of preparing the second porous carbon material using the first carbon material, the pore-forming agent includes an alkaline solution, the molar ratio of the first carbon material to the alkaline substance in the alkaline solution is (4-5):(2-3), the concentration of the alkaline substance in the alkaline solution is 0.05-0.08 mol / L, the alkaline substance in the alkaline solution includes sodium hydroxide and potassium hydroxide, the mass ratio of sodium hydroxide to potassium hydroxide is (0.95-1.05):(0.95-1.05), the calcination temperature is 750-800°C, and the calcination time is 1-2h; Preferably, the step of purifying the second porous carbon material comprises: firstly acid-washing the second porous carbon material, then washing with water until it is neutral, and then calcining the second porous carbon material at a calcination temperature of 500 to 600° C. for a calcination time of 3 to 4 hours; Preferably, in the process of preparing the porous silicon-carbon core raw material using the third porous carbon material, the molar ratio of the third porous carbon material to the silicon source gas is (4-4.3):1, and the flow rate of the silicon source gas is 1-2 m / s. 3 / h, the deposition temperature is 400-600°C, the deposition time is 4-7h, and the silicon source gas includes at least one of silicon tetrahydride and silicon dioxide.
9. A battery, characterized in that: The invention comprises a positive electrode sheet and a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer comprises the porous silicon-carbon material according to any one of claims 1 to 8.
10. An electrical device, characterized in that: The electric device comprises the battery as claimed in claim 9.
